PENGGUNAAN DEIKSIS PRONOMINA, TEMPAT, DAN WAKTU PADA NOVEL GENDUK KARYA SUNDARI MARDJUKI - Maisuri, Atika; Patriantoro, Patriantoro; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research on the pronouns' deiksis, place, and time on the novel Genduk Karya Sundari Mardjuki focuses on the description of the use of pronouns dexterity, place and time. This is in accordance with the formulation of the problem, namely: (1) How is the use of pronouns deiksis at Sundel Mardjuki's Sundel Genduk? (2) How is the use of place deixis at Sundari Mardjuki's Sundel Genduk? (3) How is the use of time deixis in Sundel Mardjuki's Sundel Genduk? This study aims to Describe the use of pronouns deiksis, place, and time on Sundel Mardjuki's Sundel Genduk and conclude it. This research uses descriptive and qualitative method. Sources of data and research data are novel Genduk Sundari Mardjuki and quotations or sentences that show the use of pronouns deiksis, place, and time. Data collection techniques used are documentation and data collection tool is a researcher as a key instrument by recording data that are quotations or sentences containing pronouns deixis, place, and time. This study uses the technique to test the validity of the data that is observational persistence and referential adequacy. Keywords: Deiksis, Pronoun, place, time, novel